2021
DOI: 10.3390/jcm10040732
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias in Muscular Dystrophies Associated with Emerinopathy and Laminopathy: A Cohort Study

Abstract: Introduction: Cardiac involvement in patients with muscular dystrophy associated with Lamin A/C mutations (LMNA) is characterized by atrioventricular conduction abnormalities and life-threatening cardiac arrhythmias. Little is known about cardiac involvement in patients with emerin mutation (EMD). The aim of our study was to describe and compare the prevalence and time distribution of cardiac arrhythmias at extended follow-up. Patients and methods: 45 consecutive patients affected by muscular dystrophy associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Clinical and echocardiographic parameters as well as cardiac biomarkers were assessed at baseline and then correlated with the clinical course of the disease. Clinical parameters included: heart failure symptoms, atrioventricular (AV) block (determined based on electrocardiographic criteria), atrial fibrillation (paroxysmal, persistent, and permanent), and atrial standstill [4]. The last one, characterized by the absence of electrical and mechanical activity of the atria, is one of the features of EDMD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and echocardiographic parameters as well as cardiac biomarkers were assessed at baseline and then correlated with the clinical course of the disease. Clinical parameters included: heart failure symptoms, atrioventricular (AV) block (determined based on electrocardiographic criteria), atrial fibrillation (paroxysmal, persistent, and permanent), and atrial standstill [4]. The last one, characterized by the absence of electrical and mechanical activity of the atria, is one of the features of EDMD.…”
Section: Methodsmentioning
confidence: 99%
“…The peripheral muscle's involvement might be benign while the main risk for patients is that of cardiovascular complications [2]. Features of typical cardiomyopathy [3] and typical arrhythmias occurring during the disease [4] have been previously described. The current study aimed to identify predictors of adverse clinical events in a long-term follow-up observation.…”
Section: Introductionmentioning
confidence: 95%
“…31 In EDMD2, malignant ventricular arrythmias which required implantation of implantable cardioverter-defibrillator (ICD) were commonly seen. 32 Subsequently, progressive ventricular dysfunction and heart failure become prominent in EDMD2 but not frequent in EDMD1, although echocardiography shows no differences of enlarged atria, dilatation of left ventricle, and left ventricular ejection fraction between EDMD1 and EDMD2. 33 Serum tenascin-C levels may be a helpful marker for at risk of cardiomyopathy.…”
Section: Cardiac Involvementmentioning
confidence: 96%
“…Atrial fibrillation/flutter and atrial standstill is common and more frequently observed in EDMD1 than EDMD2, but sudden death was quite rare in EDMD1 after pacemaker implantation 31 . In EDMD2, malignant ventricular arrythmias which required implantation of implantable cardioverter‐defibrillator (ICD) were commonly seen 32 . Subsequently, progressive ventricular dysfunction and heart failure become prominent in EDMD2 but not frequent in EDMD1, although echocardiography shows no differences of enlarged atria, dilatation of left ventricle, and left ventricular ejection fraction between EDMD1 and EDMD2 33 .…”
Section: Clinical Manifestations Of Ne Myopathymentioning
confidence: 99%
“…Arrhythmia, cardiomyopathy, atrioventricular block, strokes, heart failure, and sudden death have all been reported for patients suffering from Emery–Dreifuss muscular dystrophy [ 39 , 40 ]. Moreover, for patients suffering from Lamin A/C mutations, the cardiac features are very commonly associated with atrioventricular conduction irregularities, as well as life-threatening cardiac arrhythmias [ 41 ].…”
Section: Classification and Pathogenesis Of Muscular Dystrophiesmentioning
confidence: 99%